2017
DOI: 10.1002/jcla.22268
|View full text |Cite
|
Sign up to set email alerts
|

An improved PCRCTPP assay for the detection of ADH1B Arg48His polymorphism

Abstract: This improved PCR-CTPP assay is simple, rapid, cost-effective, and reliable, specific for the detection of ADH1B Arg48His polymorphism in most clinical diagnostic laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The two fluorescent probes used in TaqMan make genotyping accurate and fast but result in higher labour and material costs [44]. Due to its simplicity and reliability, the PCR-CTPP assay has been a popular technique for assessing SNP [45] and a newly designed PCR-CTPP has been shown to be both rapid and reliable for polymorphism detection in a clinic setting [46]. A previous study indicated that the accuracy [47].…”
Section: Discussionmentioning
confidence: 99%
“…The two fluorescent probes used in TaqMan make genotyping accurate and fast but result in higher labour and material costs [44]. Due to its simplicity and reliability, the PCR-CTPP assay has been a popular technique for assessing SNP [45] and a newly designed PCR-CTPP has been shown to be both rapid and reliable for polymorphism detection in a clinic setting [46]. A previous study indicated that the accuracy [47].…”
Section: Discussionmentioning
confidence: 99%